Perencanaan Sistem Penyaluran Air Limbah (SPAL) Dan Instalasi Pengolahan Air Limbah (IPAL) Domestik Terpusat Di Dukuh Desa Pendem Kecamatan Kembang Kabupaten Jepara - Qolbi, Muhammad Ainun; Hidayati, Nor; Rochmanto, Decky; Roehman, Fatchur; Faqih, Nasyiin; Mushthofa, Mushthofa (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2023)
omestic wastewater in Pendem villages, especially Randusari and Belik hamlets, is still not treated properly. Waste water, especially greywater, is immediately disposed of in ditches that lead to rivers. This activity can damage the river environment and pollute residents' clean water sources. The purpose of this planning is to plan the SPAL and IPAL for the residents of Dukuh Belik and Randusari so that good and proper environmental sanitation conditions are created. The results of this planning for the waste water distribution system (SPAL) are that the length of the waste water distribution pipe in Randusari Hamlet reaches 2,861.40 m while in Belik Hamlet it is 3,028.70 m, equipped with a manhole building with a diameter of 60 cm and a control tank of 50 x 50 cm. In the wastewater treatment installation, 3 units of manufactured Biofilter IPAL are used, in Hamlet Randusari, 3 RCO-100 type IPALs with a capacity of 100 m3 are used, and 2 RCO-60 type IPALs with a capacity of 60 m3 are used in Dukuh Belik. From this plan, a budget for the construction of the SPAL and IPAL Dukuh Randusari is required in the amount of Rp. 4,141,427,000.00. And for hamlet buying Rp. 2,586,384,000.00.